A62 THE UTILITY OF FECAL IMMUNOCHEMICAL TEST IN HOSPITALIZED PATIENTS: A RETROSPECTIVE CHART REVIEW. (4th March 2021) - Vantomme, E; Chetty, K; Ho, K; O'Byrne, M
Abstract: Background: Fecal immunochemical test (FIT) is a colorectal cancer (CRC) screening tool that uses antibodies to detect the globin moiety of human hemoglobin. On average, one test costs approximately $35 CAD. It has been widely validated as an effective screening tool that is both more sensitive than fecal occult blood testing, and less likely to react to non-human sources of blood, such as from dietary sources. Despite an absence of evidence for use in hospitalized patients, it is commonly ordered in this setting. Aims: To assess the value and appropriateness of FIT in hospitalized patients in an urban health authority. Methods: All FITs ordered for hospitalized patients between August 1, 2017 and June 1, 2018 in one academic hospital in Regina, Saskatchewan were examined. Of the 626 cases that were identified, information regarding demographics, clinical presentation, consultations, laboratory values, and endoscopy results were recorded. Results: Of all 626 FITs ordered, 204 were positive and 422 were negative. Hospitalist physicians ordered 41% of these FITs. Of the 197 patients with negative FITs whose clinical data were available, 39% proceeded to gastroscopy and 23% proceeded to colonoscopy/flexible sigmoidoscopy during admission. Of the 201with positive FITs whose clinical data were available, 58% proceeded to gastroscopy and 40% proceeded to colonoscopy/flexible sigmoidoscopy during admission. FIT had a sensitivity of 100% (95% CI: 94–100%) and specificity of 3% (95% CI: 0–15%) to detect abnormal colonoscopy/flexible sigmoidoscopy results while having a sensitivity of 67% (95% CI: 57–78%) and specificity of 45% (95% CI:36–55%) to detect abnormal gastroscopy. Using a composite of uninvestigated iron deficiency, age >75 or <50 years, clinically overt bleeding, endoscopy despite negative FIT, and up-to-date CRC screening as a definition for inappropriate use of FIT, we found that 7% of negative FITsand 4% of positive FITs were appropriately ordered. Conclusions: FIT tests had excellent sensitivity for lower gastrointestinal bleeding but had a high false positive rate in this population. FIT tests performed poorly in upper gastrointestinal bleeding. Using FIT for its validated purpose of CRC screening was done in a minority of cases. Importantly, 60% of patients with negative FIT tests proceeded to endoscopy, which may suggest that FITs in hospitalized patients does not significantly alter clinical decision making in a majority of cases. Funding Agencies: None